Technical Terms Translation: Translation Techniques and Quality of Automotive Terms in the Yamaha Nmax Owner’s Manual - Pradipta Dhaifan Hindami (Universitas Sebelas Maret, 2019)
In Indonesia, many types of motorcycle are produced and marketed. Most of them are made by foreign manufacturers. The manual books which are printed in foreign languages such as English may cause some problems for the motorcycle owners and users in the country. One of the problems is the translation of the technical terms in the manual books. It is thus challenging to analyze the translation techniques applied in the translation of the automotive technical terms in Yamaha Nmax Owner’s Manual, and the impact of translation techniques on the accuracy, acceptability and readability. Yamaha Nmax is one of the motorcycles with high sales rate in the country. The methods of data collection consist of content analysis and in-depth interview with the raters and respondents. The results show that there are 8 techniques used to translate the technical terms and the use of the techniques result in a translation which is in general accurate, acceptable, and readable. The technique which produces translations with high level of accuracy, acceptability and readability is established equivalent. Meanwhile, generalization tends to produce translations with low level of accuracy, while borrowing produces translations with low level of acceptability and readability.